Diagnostic Value of Bronchoalveolar Lavage Examination in Sputum Negative Patients for AFB in Suspected Pulmonary Tuberculosis (KYAMC Journal, 2021)
Background: Pulmonary tuberculosis (PTB) is one of the most common infections worldwide, more commonly among the developing countries like Bangladesh. So its early detection and prompt treatment was a challenge and the burden of diagnostic challenge was higher if the patients smear negative for Acid Fast Bacilli (AFB).Objective: Evaluate the diagnostic value of Bronchoalveolar lavage (BAL) for diagnosis of suspected Pulmonary Tuberculosis (PTB) whose sputum for AFB smear neagtive.Materials and Methods: A cross-sectional observational reserach was undertaken where 50 patients were included on the basis of specific inclusion and exclusion criteria. All patients who had negative smear for AFB but highly suspected for PTB underwent fibreoptic bronchoscopy to collect Bronchoalveolar lavage (BAL) fluid for diagnostic testing in the form of BAL for AFB and mycobacterial culture in Lowenstein Jensen medium.Results: The Male predominacy 29 (58%) was obserevd among the smear negative PTB patients. Clinically more than seventy percent (72%) presents with fever then cough with sputum and haemoptysis 62% and 32% respectively. Radiological cavitation 33 (66%) was the most common x-ray findings. After analysis of BAL for AFB about 31 (62%) patient found positive and on culture about mycobacterial growth found in 29 (58%) patients.Conclusion: Bronchoalveolar lavage had a superior diagnostic value in patients with smear negative suspected pulmonary tuberculosis.KYAMC Journal.2021;12(02): 84-87